Coinstar, Inc. Proposes Corporate Name Change to Outerwall: Outerwall Reflects Future Vision and Limitless Possibilities (PR Newswire, 2013)
Subject to receipt of stockholder approval at the Annual Meeting of Stockholders and completion of other legal formalities, Coinstar, Inc. will change its name to Outerwall Inc. The company's core businesses will retain their current brand names, Redbox and Coinstar.